Pengaruh Partisipasi Anggaran terhadap Budgetary Slack dengan Self Esteem sebagai Variabel Moderasi - Mardhiana, Made Dwi (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
Budgetary slack is an imbalance between actual budget potential and budget being drafted. Budgetary participation is often associated with budgetary slack problems. Self esteem said to be an element that reduce the symptoms of budgetary slack. The purpose of this study is to prove the empirical evidence of the effect of budgetary participation on budgetary slack with self esteem as a moderation variable. The theoretical references are agency theory and contingency theory. This research was conducted on 6 Regional Work Unit Organization (SKPD) as revenue center of Bali Province Government. The samples are Echelon II, III, and IV officials. The method used in determining the sample is purposive sampling and obtained 56 officials as sample. The technique used to collect data is questionnaire. The test used in the first hypothesis testing is a simple linear regression analysis and test of absolute difference value in testing the second hypothesis. The results of the first hypothesis testing with multiple linear regression analysis found that the budget participation has a positive effect on budgetary slack. The result of the second hypothesis testing with the test of absolute difference value found that the self esteem is as a moderation variable that weakens the relationship of budget participation to budgetary slack. The suggestion that can be given is to reduce the level of official participation by only involving officials who have high self esteem in order to reduce budgetary slack. Keywords: budgeting participation, budgetary slack, self esteem